The role of a newly discovered family of transcription factors, APIAP2, during the development of the rodent malaria parasite Plasmodium berghei - Gomes, Ana Rita Batista, 1987 (2012)
Tese de mestrado. Biologia (Microbiologia Aplicada). Universidade de Lisboa, Faculdade de Ciências, 2010